Modification of lignocellulose complexes with copper ferrocyanide compounds: influence of the cluster size on the selectivity of radiocesium sorption - Galysh, V.V.; Milyutin, V.V.; Chunikhin, O.Yu.; Kartel, M.T. (Reports of the National Academy of Sciences of Ukraine, 2014)
The possibility to obtain new combined sorbents of the lignocellulose-inorganic type based on a lignocellulose complex, obtained from apricot stones, and copper ferrocyanide is shown. The dependence between the modifier concentration in the initial solution, its content in obtained combined sorbents, the size of its agglomerates, and the sorption capacity with respect to 137Cs is determined. It is determined that increasing the concentration of copper ferrocyanide increases the content of the inorganic component in the carrier volume and increases the sorption properties of the obtained combined materials with respect to radiocesium; but the specific parameters of sorption capacity are decreased substantially at the same time. The sorbent samples with the content of the ferrocyanide phase are 4.5% in the carrier volume of characterized by the maximum values of recovery rate (94%) and distribution coefficient (7000 ml/g), but the maximum efficiency of using the mass of a modifier for the radionuclide sorption corresponds to the samples of lignocellulose-inorganic materials with the content of copper ferrocyanide of about 2–2.5%.